Dampak Pernikahan Dini terhadap Pola Komunikasi Orang Tua Dan Anak - Qiqi Nuthayati; Nirwan Syafrin; Yono Yono (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
This study focuses on the impact of early marriage on the communication patterns of parents and children which aims to investigate the communication patterns between parents and children, and investigate the impact of early marriage on the communication patterns used by parents and children, especially in Bojong Indah Village. The method used in this study is qualitative, by conducting direct observations, face-to-face interviews with informants and online through WhatsApp social media. This study explains that there are 3 communication patterns used by parents who marry early and children in Bojong Indah Village, namely: permissive communication patterns (liberating), authoritarian communication patterns (restricting) and democratic communication patterns (directing). Of the 3 communication patterns that exist between parents who marry early and their children have an impact, such as permissive communication patterns have an impact on children, namely: children feel given freedom, there is no direction from parents to children, children communicate with parents freely without feel wrong, children can do anything freely because parents always allow. The impact of authoritarian communication patterns such as: children become more closed, children are reluctant to express their wishes, children prefer to follow the wishes of their parents forcibly, children become more distant from their own parents. With the exception of democratic communication patterns that have a positive impact on children, because parents always provide direction to children without restraining the child's desires. Keywords: early marriage, communication patterns, impact